Revisiting oestrogen antagonists (clomiphene or tamoxifen) as medical empiric therapy for idiopathic male infertility: a meta‐analysis. (22nd August 2013) - Chua, M. E.; Escusa, K. G.; Luna, S.; Tapia, L. C.; Dofitas, B.; Morales, M.
Summary: The aim of this study was to synthesize and present the latest available evidence regarding the use of oestrogen antagonists as empiric medical therapy for idiopathic male infertility with oligo and/or asthenoteratozoospermia through meta‐analysis of randomized controlled trials (RCTs). Systematic literature acquisition was done for English and other foreign language biomedical databases up to March, 2013. RCTs relevant to the topic were identified and critically appraised independently by two physician reviewers. Dichotomous data of pregnancy rate and adverse events were extracted for calculation of odds ratio (OR) and 95% confidence interval (CI). Effect estimates were pooled using Peto method with fixed effect model. The continuous data of semen and endocrine parameters were calculated for the mean difference between pre‐ and post‐treatment effects, the weighted mean difference (WMD) and SD between the control and intervention group were determined and pooled using the random effects model. Inter‐study heterogeneity and publication bias were assessed. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guideline for meta‐analysis reporting was followed. Eleven RCTs of good methodological quality were included for meta‐analysis. The pooled effect estimates showed that oestrogen antagonists use was associated with a statistically significant increased pregnancy rate compared with controls (pooled OR 2.42; 95% CI 1.47–3.94; p = 0.0004). Significant increase in sperm concentration (WMD 5.24; 95% CI 2.12, 88.37; p = 0.001) and per cent sperm motility (WMD 4.55; 95% CI 0.73, 8.37; p = 0.03) were also noted. While significant elevation of serum follicle stimulating hormone (WMD 4.19 95% CI 2.05, 6.34; p = 0.0001) and testosterone (WMD 54.59; 95% CI 15.92, 93.27; p = 0.006) was associated with its use. No significant difference in adverse event was noted between oestrogen antagonists‐treated group and controls. The evidence suggests that oestrogen antagonists as empiric medical therapy for idiopathic male infertility with low non‐serious adverse event associated, may increase spontaneous pregnancy rate, improve sperm concentration and per cent sperm motility.